MENCARI HAKIKAT TUHAN (Menggali Makna Makrifat Al-Ghazali) - mutrofin mutrofin (EMPIRISMA: JURNAL PEMIKIRAN DAN KEBUDAYAAN ISLAM, 2018)
This article discusses the concept of makrifat Imam Ghazali. In this concept will be explained how a true servant is able to know the nature of God as a whole. Using multiple maqamat in attaining the level of gnosis. As according to Ghazali, that the highest levels of Sufism is makrifat. One of the tools to determine the nature of God by using qalb. Therefore, man should seek knowledge to know God. As Allah says in Hadith Qudsi "I like a hidden treasure. I want to be recognized, therefore I created beingsâ€. The creature in question in the hadith is human. Humans who will obey commands and obeys the ban on him. Keyword: Human Being, God, Maâ€™rifah and Sufism